2021
DOI: 10.1007/s00417-021-05332-8
|View full text |Cite
|
Sign up to set email alerts
|

The RAP study, report 4: morphological and topographical characteristics of multifocal macular neovascularization type 3

Abstract: Purpose To report on the morphological characteristics and regional distribution of multifocal macular neovascularization type 3 (mMNV3). Methods Twenty-two consecutive eyes of 21 patients with mMNV3 were included using multimodal imaging. The count and stage of lesions of all MNV types and the existence of exudate and hemorrhage were determined. Also, we addressed the regional distribution of MNV3 lesions between the superior-inferior and the nasal-tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Nevertheless, we found that there was no MNV1 or MNV2 elsewhere in eyes with MNV3 lesions. This finding correlates with our findings on solitary, cilioretinal, and multifocal MNV3, 5,6,8 which indicate that the main predisposing factors of this type are different from those of MNV1 and MNV2, or the development of MNV1 or MNV2 prevents the progression of MNV3.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, we found that there was no MNV1 or MNV2 elsewhere in eyes with MNV3 lesions. This finding correlates with our findings on solitary, cilioretinal, and multifocal MNV3, 5,6,8 which indicate that the main predisposing factors of this type are different from those of MNV1 and MNV2, or the development of MNV1 or MNV2 prevents the progression of MNV3.…”
Section: Discussionsupporting
confidence: 92%
“…These lesions are distributed from 500 to 1,500 µ m from the center and likely cause more fluid than an eye with one lesion would show. 11 Did the authors verify the distribution of this phenotype in both groups because it could also cause a bias when central macular thickness measurements were compared between groups?…”
Section: Confounding Factorsmentioning
confidence: 99%
“…The copyright holder for this this version posted September 15, 2022. ; https://doi.org/10.1101/2022.09. 13…”
Section: Precismentioning
confidence: 99%
“…Macrophages, VEGF-positive fibroblasts, lymphocytes, Müller cell processes, and subducted RPE cells were identified. 12, 13 Hence, ischemia and inflammatory pathways were suggested in the development and progression of type 3 MNV. 12, 13…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation